Challenges and opportunities in global mental health: a perspective from WHO. (26th September 2016) - Saxena, S.
Abstract : This paper enumerates and briefly discusses WHO's recent contributions to global mental health and the current challenges and opportunities in this area. It briefly discusses response to diversity across countries and communities, the need for innovations and global exchange of information, evidence and knowledge and raises issues like psychological interventions and human rights related to mental health.